Biomass characterization and pyrolysis towards bio-oil production - Batista, Gabriel de Freitas (2022)
One of the greatest challenges humanity has to deal with nowadays is climate change. An important strategy to mitigate climate change is replacing fossil fuels with renewable sources of energy [1]. Biomass is considered one of the world's most promising renewable energy sources, mainly due to its nearly endless availability. Worldwide, each year plants convert approximately 125 gigatons of carbon from atmosphere into biomass, which is equivalent to almost 300 million tons of oil per day [2]. There are many advantages in using biomass as an energy source, namely its carbon neutrality and being a non-polluting source. In this context, the main technologies for fuel and/or energy production from biomass are pyrolysis, gasification, or combustion.